Preclinical evaluation of a novel polyphosphazene surface modified stent. (1st November 2016) - Koppara, Tobias; Sakakura, Kenichi; Pacheco, Erica; Cheng, Qi; Zhao, XiaoQing; Acampado, Eduardo; Finn, Aloke V.; Barakat, Mark; Maillard, Luc; Ren, Jane; Deshpande, Mahesh; Kolodgie, Frank D.; et al.
Abstract: Background: Treatment options for patients with coronary artery disease at high risk for bleeding complications are limited. The aim of the current preclinical study was to evaluate neointimal coverage, endothelial recovery, inflammation and thrombogenicity in a novel thin-strut (71 μm thickness) Cobalt Chromium (CoCr) stent modified with a nano-thin Polyzene®-F (PzF) surface coating. Methods and results: Twenty-eight single PzF nano-coated stents and 20 bare metal control stents (BMS) were implanted in the coronary arteries of 24 pigs, with scheduled 5- (n = 5), 28- (n = 13), and 90-day (n = 6) follow-up in addition to overlapping configuration (n = 6 each), examined at 28-days. Histomorphometric analysis showed significantly lower neointimal thickness in PzF nano-coated stents than BMS controls at both 28- and 90-days (p = 0.023 and 0.005) and reduced inflammation (p = 0.06 and 0.13). Endothelial coverage over luminal surfaces at all time points was similar between nano-coated stents and BMS controls. We conducted supplementary in-vitro experiments using human monocytes and an ex-vivo swine carotid-jugular arterio-venous shunt model to better understand the healing properties afforded by the PzF nano-coating. Overall, the PzF-nano-coating showed reduced monocyte adhesion and thrombus formation compared to the un-coated controls. Conclusions: Stents modified with a nano-thin PzF-coating implanted in healthy swine indicate favorable vascular healing properties shown by reduced neointimal hyperplasia and inflammation, along with resistance to thrombus formation in an ex-vivo shunt model over unmodified stents.